O ensino da cartografia e a utilização de geotecnologias em situações de aprendizagem na geografia escolar - Silva, Maria Lucia Santos da (2010)
The school geography has many possibilities for approaches to geographic content to arouse student interest and provoke questions, one of the possibilities, working with maps. Thus, we can adopt the methodology of the cartographic language for the construction of geographical knowledge by developing the ability to understand reality from standpoint of their own space. This research has as main objective the evaluation and creation of learning situations using geo-technologies in the teaching of cartography in geography. Were developed proposals for activities buoyed by the knowledge of the properties of language mapping with the use of geo-technologies, as GPS, GIS and Remote Sensing Images. Issues of basic cartography - orientation, scale and geographical coordinates - and thematic mapping were discussed, focusing on construction and map reading. We performed the evaluation of the proposed learning situations with students from 76th and 7th year of elementary school in a public school of São José dos Campos, Brazil. The evaluation showed that the use of geo-technologies aspect in teaching and learning, has provided significant gains and the introduction of an innovative practice in a situation of conventional classroom learning environment has provided an attractive and stimulating to students participating in the research